2016
DOI: 10.1182/blood-2015-09-625343
|View full text |Cite
|
Sign up to set email alerts
|

Influence of immunoglobulin isotype on therapeutic antibody function

Abstract: Monoclonal antibody (mAb) therapeutics are revolutionizing cancer treatment; however, not all tumors respond, and agent optimization is essential to improve outcome. It has become clear over recent years that isotype choice is vital to therapeutic success with agents that work through different mechanisms, direct tumor targeting, agonistic receptor engagement, or receptor-ligand blockade, having contrasting requirements. Here we summarize how isotype dictates mAb activity and discuss ways in which this informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 73 publications
1
79
0
2
Order By: Relevance
“…This is consistent with findings by Beers et al that IgG isotypes may be of more importance than the total IgG level. 8 Consistent with our pilot findings, Karlsson and colleagues showed that total IgG antibody response does not correlate with functional assays of pneumococcal killing. 5 Thus, from this limited data, it appears that clinicians should not rely on quantitation of IgGs nor their subclasses when deciding whether or not to vaccinate patients with MM.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with findings by Beers et al that IgG isotypes may be of more importance than the total IgG level. 8 Consistent with our pilot findings, Karlsson and colleagues showed that total IgG antibody response does not correlate with functional assays of pneumococcal killing. 5 Thus, from this limited data, it appears that clinicians should not rely on quantitation of IgGs nor their subclasses when deciding whether or not to vaccinate patients with MM.…”
Section: Discussionsupporting
confidence: 89%
“…the length of the hinge and the number and orientation of disulfide bonds differs between isotypes, leading to variable flexibility between the two Fab arms and between Fab and Fc regions. These differences in the hinge region affect Fc receptor binding and Fc-mediated effector functions, but may also impact the Fab-mediated, direct effector mechanism of antibodies [14] - as outlined in more detail for IgG2 and IgG3 isotypes in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, data suggest that a hierarchy exists with respect to the effectiveness of cross-linking by different FcR, with FcγR IIB being most active and FcγRIIA being inhibitory [57]. This suggests that careful consideration of the framework of TNFRSF-targeting antibodies will need to be considered, with IgG1 subtypes perhaps being most efficacious [58] for cross-linking and impeding regulatory T cells, and raises the possibility that trimeric ligands may be a more optimal approach for stimulating TNFRSF in vivo. IgG1 molecules may, of course, lead to deletion of other subsets of cells expressing the targeting TNFSFR, and overt removal of Treg in combination with systemic inflammation may reveal unanticipated toxicities.…”
Section: Promoting Tnfsfr Responsesmentioning
confidence: 99%